EFFECTS OF JOULE HEATING ON MHD NATURAL CONVECTION IN NON-ISOTHERMALLY HEATED ENCLOSURE - Öztop, Hakan Fehmi; Al-Salem, Khaled (Turkish Soc Thermal Sciences Technology, 2012)
In this numerical work, effects of joule heating on natural convection in non-linearly heated square enclosure from right vertical wall were investigated for different Rayleigh numbers and Hartmann numbers. The cavity was considered with adiabatic horizontal walls and cooled left wall. Finite volume method was used to solve governing equations. The calculations have been performed for different Rayleigh numbers (Ra = 10(4), 5x10(4) and 10(5)), Joule parameter (J = 0.0, 3.0 and 5.0) and Hartmann number (Ha = 0, 10, 20 and 50). Obtained results are illustrated with streamlines, isotherms, temperature and velocity profiles and mean Nusselt number. It is found that the flow become weaker near the right corner of the cavity due to non-isothermal boundary condition. Both Hartmann number and Joule parameter have important effect on heat transfer and fluid flow.
Keywords: Non-isothermal heater; Natural convection; Joule effect; MHD